Three-rooted mandibular first primary molar in a 5.5-year-old child: a case report with a brief review - Reyhaneh Faghihian; Elahe Asnaashari Esfahani (مجله پزشکی دانشگاه علوم پزشکی تبریز)
Knowing the morphology of primary teeth and their difference with permanent teeth is essential for pulp treatment and tooth extraction. The first primary molar has a simple root canal system with one canal in the mesial root and one canal in the distal root. The presence of extra roots in the mandibular first primary molar is rare. In this article, we report a 5.5-year-old boy with three-rooted first molar. A 5.5-year-old boy presented with a complaint of pain in the right side of the lower jaw. In the clinical examination, we noticed that the crown of the tooth was angular, and in the radiographic examination, we noticed the presence of the third root in this tooth. The diversity of root canal morphology is a challenge for successful diagnosis and treatment of pulp; therefore, it is very important to have knowledge about it. Practical Implications. In this study, the prevalence of three-rooted mandibular first molar and the importance of the presence of extra roots in the teeth have been discussed. Additionally, a case with an extra root is reported in this report